Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00705-013-1970-6
|View full text |Cite
|
Sign up to set email alerts
|

Gammasphaerolipovirus, a newly proposed bacteriophage genus, unifies viruses of halophilic archaea and thermophilic bacteria within the novel family Sphaerolipoviridae

Abstract: A new family of viruses named Sphaerolipoviridae has been proposed recently. It comprises icosahedral, tailless haloarchaeal viruses with an internal lipid membrane located between the protein capsid and the dsDNA genome. The proposed family Sphaerolipoviridae was divided into two genera: Alphasphaerolipovirus, including Haloarcula hispanica viruses SH1, PH1 and HHIV-2, and Betasphaerolipovirus, including Natrinema virus SNJ1. Here, we propose to expand the family Sphaerolipoviridae to include a group of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 57 publications
(111 reference statements)
1
46
0
Order By: Relevance
“…Moreover, in-frame deletion of the VP2-encoding gene had no observable effect on virion assembly or infectivity, indicating that the gene is dispensable under laboratory growth conditions (79). Interestingly, unlike other SSV1 VPs, VP2 is not specific to fuselloviruses but also is encoded by unrelated proviruses of the euryarchaeon Archaeoglobus veneficus SNP6 (80), Sulfolobus turreted icosahedral virus 2 (81), and bacterial viruses of the recently established family Sphaerolipoviridae (82). Such patchy phyletic distribution of vp2-like genes in fuselloviruses, its conservation in other archaeal and bacterial viruses, and the dispensability of VP2 for SSV1 infectivity indicate that the vp2 gene has been acquired relatively late in the history of fuselloviruses from a different group of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in-frame deletion of the VP2-encoding gene had no observable effect on virion assembly or infectivity, indicating that the gene is dispensable under laboratory growth conditions (79). Interestingly, unlike other SSV1 VPs, VP2 is not specific to fuselloviruses but also is encoded by unrelated proviruses of the euryarchaeon Archaeoglobus veneficus SNP6 (80), Sulfolobus turreted icosahedral virus 2 (81), and bacterial viruses of the recently established family Sphaerolipoviridae (82). Such patchy phyletic distribution of vp2-like genes in fuselloviruses, its conservation in other archaeal and bacterial viruses, and the dispensability of VP2 for SSV1 infectivity indicate that the vp2 gene has been acquired relatively late in the history of fuselloviruses from a different group of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have shown that the VP11-encoding gene (ORF11) is exclusively found in P23-77 and has no homologs in the related sphaerolipovirus IN93 or associated proviruses (4,34,35). The only similarity we detected in data bank searches was to a protein sequence derived from Meiothermus timidus, indicating the presence of a P23-77-like provirus.…”
Section: Vp11 Sequence Analysismentioning
confidence: 82%
“…With respect to extreme thermophilic bacteria, the virus studied best on the structural level is P23-77, a strictly lytic phage infecting Thermus thermophilus ATCC 33923 (1,2,3). P23-77 is a representative of the novel Sphaerolipoviridae, comprising viruses infecting members of two domains of life, namely, extreme halophilic archaea of the family Halobacteriaceae and thermophilic bacteria of the family Thermaceae (4). All the family members have similar virion morphologies.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…However, some of these minor proteins might form terminal filaments of PFV1. Examples of interchangeable gene cassettes encoding receptor-binding proteins are known from several different families of archaeal viruses, including Lipothrixviridae, Sphaerolipoviridae, and Fuselloviridae (37)(38)(39)(40). Most of the minor structural proteins of PFV1 are encoded in the vicinity of the three major virion proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%